2007
DOI: 10.1353/sof.2007.0098
|View full text |Cite
|
Sign up to set email alerts
|

Age, Cohort and Perceived Age Discrimination: Using the Life Course to Assess Self-reported Age Discrimination

Abstract: Self-reported discrimination is linked to diminished well-being, but the processes generating these reports remain poorly understood. Employing the life course perspective, this paper examines the correspondence between expected age preferences for workers and perceived age discrimination among a nationally representative sample of 7,225 working women, followed between 1972-1989. Analyses find that perceived age discrimination is high in the 20s, drops in the 30s and peaks in the 50s. This curvilinear pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 71 publications
5
87
2
Order By: Relevance
“…Their analysis suggested that perceived discrimination has two peaks: in the 20s and the 50s. These peaks lower in the 30s (Gee, Pavalko, & Long, 2007). Given these findings, it could be informative to add additional comparison groups in future studies.…”
Section: Discussionmentioning
confidence: 92%
“…Their analysis suggested that perceived discrimination has two peaks: in the 20s and the 50s. These peaks lower in the 30s (Gee, Pavalko, & Long, 2007). Given these findings, it could be informative to add additional comparison groups in future studies.…”
Section: Discussionmentioning
confidence: 92%
“…27 Indirect evidence comes from research on age discrimination, which shows that reports of age discrimination in the workplace vary as women move from being young job seekers to midcareer employees to retirees. 28 Hence, the forms and frequency of discrimination may change with age. Moreover, the effects of certain types of discrimination may reverberate across the life course and reinforce one another.…”
Section: ---24mentioning
confidence: 99%
“…These changes could be conceptually and statistically modeled as trajectories. 27,28,33,34 Second, the idea of transitions is not limited to moving from one life stage to another (e.g., work to retirement), nor is the issue of "age" simply one of biology. Both of these issues are generalizable to other phenomena.…”
Section: ---24mentioning
confidence: 99%
“…The response alternatives to this question were 'yes', 'no', and 'don't know'. This self-reported measure of age discrimination is identical to the spirit of the one used in the EBS and it has been suggested that self-reported age discrimination is a valid indicator of unfair treatment (Gee, Pavalko & Long 2007). The internal response rate on this question was high, with only 1.9 per cent (139 individuals) not responding to this question.…”
Section: Analysed Items and Methods Of Analysesmentioning
confidence: 97%